HUBUNGAN ANTARA DUKUNGAN KELUARGA, MOTIVASI DAN STIGMA LINGKUNGAN DENGAN PROSES KEPATUHAN BEROBAT TERHADAP PENDERITA TB PARU DI WILAYAH KERJA PUSKESMAS GANG SEHAT - Muhardiani, Muhardiani; Mardjan, Mardjan; Abrori, Abrori (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Pulmonary tuberculosis patients affected by family support, motivation, thus affecting the environmental stigma treatment process resulting lack treatment compliance. If the drugs are not taken in accordance with the provisions it would appear active tuberculosis germs that are resistant to the drug, if this continues to happen and continue to spread these germs, active tuberculosis drug control will be more difficult to implement and the healing process will be longer Pulmonary TB.This study aimed at finding out the correlation of family support, motivation and environmental stigma towards Pulmonary TB patients compliance with medication at work area of Gang Sehat health center.Using analytical observation, as well as cross sectional approach, 78 samples participated in this study. Each variable was tested by using chi square test.The study revealed that there were correlation of family support (PR = 1,539, p value = 0,028,), motivation (PR = 1,485, p value = 0,043,), environmental stigma (PR = 1,503, p value = 0,034,)and pulmonary TB patients compliance with medication at work area of Gang Sehat health center Advice for the family and the community is expected to understand and accept people with TB in their environment and be able to receive information from health professionals about the disease Pulmonary TB so as to prevent and eliminate the environmental stigma against pulmonary TB disease, so patients can petuh take medication regularly.Keywords : family support, motivation, environmental stigma,TB patient compliance